Application of floating fly ash-bottom ash for acid mine drainage remediation - Husada, Muhamad Hadid; Fauzi, Anas Miftah; Mansur, Irdika; Suharyono, Suharyono (Brawijaya University, 2025)
Acid mine drainage (AMD) is formed because rocks containing sulfide minerals, such as pyrite (FeS?), are exposed to oxygen and water. AMD treatment is generally carried out with lime, but this method is relatively expensive and unsustainable. Fly ash-bottom ash (FABA), a type of coal combustion waste can potentially replace lime in treating acid mine drainage (AMD). This study aimed to elucidate the potential use of FABA to neutralize pH of AMD. The method used was a floating FABA system using styrofoam with three treatments: floating FABA with dimensions (cm length x cm width x cm height) of 33x33x8 (F1 30), floating FABA of 28x28x8 (F2 25), and floating FABA of 23x23x8 (F3 20). The floating FABA consisted of 85% FABA and 15% cement, with a 120 L AMD. The results showed that the F1 30 treatment reached a pH of 6.06 from an initial pH of 4.2 within 3 days. The floating FABA application also reduced the concentration of heavy metals (Fe and Mn) and total suspended solids (TSS) in the F2 25 treatment. Micro XRF analysis indicated a high element distribution in the floating treatment zone, supporting the neutralization mechanism of precipitation and adsorption. The results of the statistical analysis showed no significant difference between treatments, indicating that all treatments were effective and could be considered based on cost efficiency and retention time. Overall, the floating FABA application increased pH and progressively reduced heavy metal content, supporting its use as an efficient and sustainable AMD neutralization solution.